(untitled) (Revista Electrónica Calidad en la Educación Superior, 2024)
The academic departments of higher education institutions are acquiring important and relevant experience in the execution of the tasks that are required for the quality certification processes, so it is imperative that this experience be used to establish common lines in the search of efficiency and effectiveness in institutional management and the use of resources. The objective of this research focuses on the study and analysis of the activities that are carried out instinctively and unofficially as part of the self-evaluation process of the academic programs of the Instituto Tecnológico de Costa Rica.